Efeito da adição da borra de babaçu na dieta de ovinos em terminação sobre o perfil de ácidos graxos do conteúdo abomasal e estimativa da biohidrogenação ruminal - SANTOS, Gabriela Oliveira dos (2022)
The aim of the present study was to evaluate the effect of the addition of babassu lees in the diet of finishing sheep on the fatty acid profile of the abomasal content and the estimate of rumen biohydrogenation. Four experimental diets with increasing levels of addition of babassu BB lees (0, 5, 10 and 15%) of dry matter (DM) were evaluated. The experimental design was completely randomized, considering the initial weight as a covariate, with four treatments and seven replications. Twenty-eight crossbred, castrated sheep (24.66 ± 4.06 kg of initial weight and 60 ± 15 days of mean age) were confined for a period of 60 days. Then, the animals were slaughtered and one sample of abomasal digesta per animal was collected, lyophilized and vacuum-packed for later determination of fatty acids. Data were subjected to analysis of variance and when significant, polynomial contrasts were evaluated to determine linear and quadratic effects of different treatment levels. Effects were considered significant when P < 0.05 and considered a trend when P < 0.10. The addition of increasing levels of babassu sludge linearly increased the consumption of dry matter (P = 0.003) and fatty acids (P < 0.001) capric (10:0), lauric (12:0), myristic (14:0) , palmitic (16:0), stearic (18:0) and for total fatty acids (FA). Oleic acid consumption (c9-18:1) also increased linearly (P= 0.011), however, its concentration in the abomasum did not differ (P > 0.05) with the addition of increasing levels of babassu sludge in the diet. No effect (P > 0.05) was observed for linoleic (18:2 n-6) and linolenic (18:3 n-3) fatty acids on abomasal content. The concentration of stearic acid (18:0, end product of biohydrogenation) in the abomasum content tended to decrease linearly (P < 0.10), which is related to the lower biohydrogenation of the 18:2 n-6 (P = 0.038) and complete biohydrogenation (P = 0.002) with the addition of increasing levels of babassu sludge in the sheep diet. The inclusion of babassu sludge at the level of 15% in the diet reduced the complete ruminal biohydrogenation of fatty acids, which may result in a higher concentration of intermediate acids from biohydrogenation in products originating from ruminants (meat or milk).